Individualized activity recommendation based on a physical fitness assessment increases short- and long-term regular physical activity in people with multiple sclerosis in a retrospective cohort study - van der Ven, Eva; Patra, Stefan; Riemann-Lorenz, Karin; Kauschke, Katrin; Freese-Schwarz, Katrin; Welsch, Götz; Krause, Nicole; Heesen, Christoph; Rosenkranz, Sina Cathérine (Frontiers in Neurology, 2024)
Background Despite the evidence of beneficial effects of physical activity (PA), people with multiple sclerosis (pwMS) are less physically active than the general population. To increase PA in pwMS, we developed a structured individually tailored PA promotion program which is conducted within clinical practice in a university-based outpatient clinic since 2016. This study serves as retrospective quality control of this program. Objective In a retrospective cohort study, we assessed the physical fitness of pwMS and the impact of the program on short- and long-term PA changes and behavioral determinants. Methods The program consisted of four appointments each 2–4 weeks apart. Spiroergometric test results of female pwMS were compared to female non-MS controls who underwent a voluntary physical fitness analysis. The short version of the Freiburger questionnaire, self-developed questions and the modified Physical activity screening questionnaire (PASQ) were sent to all participants assessing the PA levels before the program, 3 months after the program (short-term), and at the time of the survey (long-term). Additionally, established questionnaires assessed behavioral determinants before the program and long-term. Results A total of 166 participants [mean age 38.32 (± 10.61 SD), mean EDSS 2.30 (±1.29 SD)] and mostly females (63.3%, n = 105) were included in the study and started the program. A total of 136 participants completed the program. Out of these 63.9% (n = 87) answered the questionnaires in 12.38 (±11.34 SD) months after finishing the program. At baseline female pwMS (n = 100) showed a lower physical fitness in comparison to non-MS controls (n = 26) (maximal workload (Watts): 138.86 ± 37.85 vs. 191.73 ± 45.25, p < 0.001; peak oxygen consumption (ml min−1 kg−1): 26.40 ± 7.23 vs. 31.56 ± 10.10, p = 0.020). pwMS were more regularly active in short- (62.1%) and long-term (55.2%) compared to baseline (24.2%, p < 0.001). Among the activated participants, we observed improved internal motivation (p = 0.002) and decreased perception of barriers (p = 0.006) compared to baseline. Conclusion PwMS showed a lower physical fitness in comparison to non-MS controls. An individually tailored PA promotion program might improve behavioral determinants and thereby increase short- and long-term PA levels of pwMS.